Effect of crop residue and potassium management practices on productivity and economics of conservation agriculture based maize (Zea mays)-wheat (Triticum aestivum) cropping system - M, RAGHAVENDRA; SINGH, Y V; DAS, T K; MEENA, M C (The Indian Journal of Agricultural Sciences, 2017)
A field experiment was conducted in kharif and rabi seasons of 2014-2016 at ICAR-IARI, New Delhi to study the effect of crop residue and potassium (K) on productivity and economics of maize (Zea mays L.) and wheat (Triticum aestivum L.) under conservation agriculture (CA) based maize-wheat cropping system. The experiment was conducted in split plot design with four levels of crop residue in main plot, viz. no crop residue (CR), 2.0 tonnes/ha CR, 4.0 tonnes/ha CR, 6.0 tonnes/ha CR and five potassium levels, viz. no K, 50% RDK, 100% RDK, 150% RDK, 50% RDK+KSB in sub-plots. Results revealed that the yield attributes, grain and stover/straw yield were significantly influenced by the crop residue and K management practices over the control in both crop during both the years. Treatment with 50% RDK+KSB showed the significantly highest values of all yield attributes like, number of grains/cob, grain weight/cob, test weight and grain (4.91, 5.39 tonnes/ha) and stover yield (8.41, 9.07 tonnes/ha) in maize. In wheat also number of spikes/m2, grains/spike, spike weight, test weight and yield (5.16, 5.45 tonnes/ha) and straw yield were significantly higher over the control and 50% RDK. However this treatment was at par with 100% RDK and 150% RDK. Among the residue management practices 4.0 tonnes/ha CR registered significantly higher yield attributes, grain yield and stover/straw yield over no crop residue and 2.0 tonnes/ha CR and it was on par with 6.0 tonnes/ha CR in maize and wheat crops. The highest cost of cultivation was reported in 150% RDK and lowest cost of cultivation, highest gross returns, net returns and B: C ratios in maize and wheat were recorded in 50% RDK+KSB. Among residue management practices no CR registered the highest net returns and these were on par with 2 tonnes/ha CR in both the years of maize. However, in wheat highest returns were reported with 4.0 tonnes/ha CR and this was statistically at par to all the residue management practices except no CR. In both the crops, no CR showed highest B: C ratio followed by 2.0 tonnes/ha CR and 4.0 tonnes/ha CR. Lowest B: C ratio was recorded with 6.0 tonnes/ha CR. The strong correlation was observed between different yield attributes and yield in both the crops. Thus, application of 4.0 tonnes/ha CR and 50% RDK+KSB was cost effective, eco-friendly and sustainable K management practices under CA based maize-wheat cropping system and this may be recommended to farmers for adaptation.